Self-feeding molasses mixed with urea, phosphoric acid and water with or without ethyl alcohol to beef heifers. II. Meat evaluation study. - Richardson, D.; Mackintosh, D.L.; Merkel, R.A. (Kansas Agricultural Experiment Station, 2011)
The details of management and feeding of animals involved in this test are given in part I of this report. Five wholesale rib cuts from each lot were obtained at the time of slaughter for cooking, palatability, mechanical separation and chemical tests. These tests were conducted to determine the effect of the protein supplement upon the meat produced.
Keywords: Beef; Urea; Phosphoric acid; Ethyl alcohol